PROTECTION FROM VIOLENCE AND HARASSMENT AT WORK IN INTERNATIONAL LEGAL STANDARDS - Jašarević, Senad R; Božičić, Darko M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
New circumstances in the world have led to an increase in social violence and violence at work. Combating against various forms of workplace violence in recent years has been the focus of many countries. This year the International Labor Organization (ILO) has issued special documents on this (Convention 190 and Reccomendation 206). These are the first international standards that integrally address the problem of work-related violence. In addition to presenting international regulations on violence and harassment at work, the paper deals with the forms, characteristics and specificities of violence at work.